2021
DOI: 10.1096/fj.202002197r
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin activates thermogenesis of brown and white adipose tissue in high‐fat diet‐fed C57BL/6 mice by shaping the gut microbiota

Abstract: Increasing energy expenditure by activating thermogenesis in brown and beige adipocytes is a critical approach to protect against obesity. Here, we investigated the action and mechanism of a natural polymethoxyflavone on adaptive thermogenesis in high-fat diet-induced obesity mouse model. Nobiletin treatment significantly ameliorated obesity, alleviated the whitening of brown adipose tissue, and promoted browning of white adipose tissue in mice fed a high-fat diet. Gut microbiota analysis and metabolomic profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…A decrease in the Firmicutes/Bacteroidetes ratio and Proteobacteria abundance might be the triggering factor for emergence of brown adipocytes in WAT (Liao et al 2018). Consistent with these findings, fecal transplants of nobiletin-treated mice also upregulated factors involved in thermogenesis and mitochondrial biogenesis, including UCP1, PRDM16, Cidea, mitochondria transcription factor A [Tfam], and nuclear respiratory factor 1 [NRF1]), in BAT and iWAT of HFD-fed recipient mice (Kou et al 2021). Thus, evidence from a range of studies supports the beneficial effects of food phenolics on fat browning may be due, at least in part, to the regulatory actions of gut bacteria.…”
Section: Gut Microbiotamentioning
confidence: 56%
“…A decrease in the Firmicutes/Bacteroidetes ratio and Proteobacteria abundance might be the triggering factor for emergence of brown adipocytes in WAT (Liao et al 2018). Consistent with these findings, fecal transplants of nobiletin-treated mice also upregulated factors involved in thermogenesis and mitochondrial biogenesis, including UCP1, PRDM16, Cidea, mitochondria transcription factor A [Tfam], and nuclear respiratory factor 1 [NRF1]), in BAT and iWAT of HFD-fed recipient mice (Kou et al 2021). Thus, evidence from a range of studies supports the beneficial effects of food phenolics on fat browning may be due, at least in part, to the regulatory actions of gut bacteria.…”
Section: Gut Microbiotamentioning
confidence: 56%
“…It has been found that some natural products, such as Corylin (Chen, Kuo, Leu, & Wang, 2021), Nobiletin (Kou et al, 2021) and Trans ‐Cinnamic acid (Kang, Mukherjee, & Yun, 2019) can increase energy expenditure to ameliorate glucose and lipid metabolism disorders by increasing BAT activity and inducing browning of WAT. Our data showed that the weight loss effect of rutin on mice may be related to increasing the thermogenesis of BAT and IWAT and inhibiting lipid accumulation activity in adipose tissue and liver tissue to decrease the weight of adipose and liver in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that some natural products, such as Corylin (Chen, Kuo, Leu, & Wang, 2021), Nobiletin (Kou et al, 2021) and Trans-Cinnamic acid (Kang, Mukherjee, & Yun, 2019) can increase energy expenditure to ameliorate glucose and lipid metabolism disorders by increasing BAT activity and inducing browning of WAT. Our data showed that the weight loss effect of rutin on mice may be related to increasing the thermogenesis of BAT and IWAT and inhibiting lipid accumulation activity in adipose tissue and liver tissue F I G U R E 7 Rutin played multiregulatory roles in inhibiting obesity, reducing blood glucose and lipid levels, improving insulin resistance, enhancing energy expenditure and mitochondrial biogenesis, and inducing browning of IWAT and activating BAT, which has potential therapeutic significance for the treatment of obesity and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…6 When taken orally, a fraction of nobiletin was absorbed by the small intestine and affected the distal organs or tissues through circulation; most of the rest reached the large intestine to be metabolized by the microbiota. 7 Many studies reported the favorable biological effects of nobiletin for health, such as antihypertension, 8 anticancer, 9 anti-inflammation, antiobesity, 10 and antiaging 11 in the endocrine system. Thus, nobiletin may have an ideal antidiabetes effect, but the results seemed unsatisfactory, for several studies failed to verify its antihyperglycemia effect in mice with streptozocin (STZ)induced hyperglycemia.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The chemical essence of nobiletin is polymethoxyflavonoid and could be easily extracted from the peels of oranges and lemons . When taken orally, a fraction of nobiletin was absorbed by the small intestine and affected the distal organs or tissues through circulation; most of the rest reached the large intestine to be metabolized by the microbiota . Many studies reported the favorable biological effects of nobiletin for health, such as antihypertension, anticancer, anti-inflammation, antiobesity, and antiaging in the endocrine system.…”
Section: Introductionmentioning
confidence: 99%